Kedudukan Non-Muslim Dalam Qanun Jinayat Aceh (Studi Analisis Qanun Nomor 6 Tahun 2014 Pasal 5 Huruf c Menurut Maqashid Syariah Jasser Auda) - Abiyun (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
The research will focus on how the implementation of Qanun jinayat itself, and how the position of Non-Muslims in Qanun jinayat when viewed with Maqashid Shari'ah Jasser Auda. As a city that has a majority Muslim population, Aceh has customs and culture that can be said to be integrated with Islam itself. Therefore, Aceh is a special province with Qanun or Islamic law formulated as a legal umbrella in accordance with Qanun Number 6 of 2014 concerning Jinayat Law. However, the Qanun based on Islamic law will definitely intersect with the Non-Muslim population in Aceh, so there are often misunderstandings and confusion among the community